Present Situation and Problems of Cysticercosis in Animal in Bali and Papua - Dharmawan, Nyoman Sadra; Swastika, Kadek; Putra, I Made; Wandra, Toni; Sutisna, Putu; Okamoto, Munehiro; Ito, Akira (Jurnal Veteriner; Vol 13 No 2 (2012), 2013)
Cysticercosis zoonotic parasitic disesase caused by Taenia solium larva, is a major public healthproblem. Cysticercosis results from the development of larval tapeworms in humans harboring adult T.solium or from ingesting soil containing eggs shed in the feces of humans, in areas where there are nolatrines. Humans are accidental intermediate hosts and pigs are the normal intermediate hosts. Clinicallythey are most serious when located in the central nervous system or in the eye where they persist formonths to years. Cysticercosis occurs worldwide primarily in developing country where pigs are raised,pork consumed and poor sanitation allows pigs’ access to human faeces. The occurance of the diseases isexpected to increase in relation to the growing demand for pork in those countries. In Indonesia cyticercosisis still a very important health problem, especially in Bali and Papua. The majority of the populations inBali and Papua are Hindus and Protestants/Catholics, respectively, so pork widely consumed in thoseislands. This brief review summarizes the present situation and problems of cysticercosis in animal inBali and Papua. Epidemiological data of the diseases were obtained from several sources.
Keywords: cysticercosis, animal, Bali, Papua